Entre estética e política: fazer cidade fazendo festa - Tavares, Bruno (Universidade Federal de São Carlos, 2023)
The present work seeks to analyze the dispute for the use and circulation of the Santist territory, as a focus on the central neighborhoods. The insular territorial portion of the city is tiny and highly elitist as we advance toward the beachfront. On the other hand, the distant portions of the sea are progressively deprioritized in the strategic planning of the commodification of the Santist territory. In dialogue with the international literature on clubber culture, but also with authors who bring the debate on partying to the Latin American context, I aim to build an interface for discussion of the aesthetics proposed by Boiler Ruim, the city's underground clubber party; and Alegra Centro, an architectural reform project in the Centro neighborhood. For this, a bibliographic survey was carried out on the role of the central neighborhoods in the growth of Santos to be added to the literature on partying. Interviews were conducted with the organizers of Boiler Ruim, while the analysis of the documents that regulate and publicly present the Alegra Centro composed the research methodology. It was possible to list discursive elements expressed in the construction of the party that allowed to draw parallels and dissidences of Boiler Ruim with Alegra Centro, shedding light on the dispute between hegemonic and dissident forms of feeling and modifying the city. Keywords: party, clubber, urban space, aesthetics; gentrification
Between aestethics and politics: making a city by having party
Keywords: Festa; Clubber; Espaço urbano; Estética; Gentrificação; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA